А^2-9b^2/3ab : (1/3b - 1/a) при а = 8 целых 4/7 b= 4 целых 1/7 получилось, но потом путаница какая-то

stanislavcoola stanislavcoola    1   08.06.2019 20:50    0

Ответы
Мижоп Мижоп  07.07.2020 21:46
\frac{a^2-9b^2}{3ab} :( \frac{1}{3b}- \frac{1}{a})= \frac{(a-3b)(a+3b)}{3ab} :( \frac{a-3b}{3ab} )=\frac{(a-3b)(a+3b)}{3ab}* \frac{3ab}{a-3b}=a+3b

а = 8 целых 4/7 b= 4 целых 1/7

a+3b=8 \frac{4}{7}+3*4 \frac{1}{7}= \frac{60}{7}+ \frac{3*29}{7} = \frac{147}{7}=21

ответ 21
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра